The clinical significance of apoptosis and M30 expression in colonic cancer progression. (14th June 2013) - Kykalos, Stylianos; Dimitroulis, Dimitrios; Ntikoudi, Evangelia; Karayiannakis, Anastasios
Abstract: Background/aim : The aim of this study is to identify the significance of M30, an early apoptosis indicator, in colorectal cancer and its liver metastasis. Patients and methods : The expression of M30 was immunohistochemically estimated at colonic and liver metastatic tissues of 66 patients. The results were correlated to clinical and pathological features of the tumors. Results : High expression of M30 was observed in 15.5% of cases. No metastatic tissue showed expression of M30, while stage D tumors (metastasis included) showed a statistic significant lower expression of M30, when compared to earlier tumor stages. Conclusion : Low expression of M30 implies the development of resistance mechanisms against apoptosis, facilitating the progression of colon cancer.